Modulation of the Gut Microbiota-farnesoid X Receptor Axis Improves Deoxycholic Acid-induced Intestinal Inflammation in Mice. (8th January 2021) - Xu, Mengque; Shen, Yuqin; Cen, Mengsha; Zhu, Yubin; Cheng, Fangli; Tang, Linlin; Zheng, Xia; Kim, John J; Dai, Ning; Hu, Weiling
Abstract: Background and Aims: Inflammatory bowel disease (IBD) is associated with gut dysbiosis and dysregulation of bile acid metabolism. A high luminal content of deoxycholic acid (DCA) with consumption of a Westernised diet is implicated in the pathogenesis of IBD. The aim of the study is to explore the role of intestinal microbiota and bile acid metabolism in mice with DCA-induced intestinal inflammation. Methods: Wild-type C57BL mice, 4 weeks old, were fed with AIN-93G (control diet), AIN-93G+0.2% DCA, AIN-93G+0.2% DCA+6 weeks of fexaramine (FXR agonist), or AIN-93G+0.2% DCA+antibiotic cocktail, for 24 weeks. Histopathology, western blotting, and qPCR were performed on the intestinal tissue. Faecal microbiota was analysed by 16S rDNA sequencing. Faecal bile acid and short chain fatty acid (SCFA) levels were analysed by chromatography. Results: Gut dysbiosis and enlarged bile acid pool were observed in DCA-treated mice, accompanied by a lower farnesoid X receptor (FXR) activity in the intestine. Administration of fexaramine mitigated DCA-induced intestinal injury, restored intestinal FXR activity, activated fibroblast growth factor 15, and normalised bile acid metabolism. Furthermore, fexaramine administration increased the abundance of SCFA-producing bacteria. Depletion of the commensal microbiota with antibiotics decreased the diversity of the intestinal microbiota, attenuated bile acid synthesis, and reduced intestinal inflammation induced by DCA. Conclusions: DCA induced-intestinal inflammation is associated with alterations of gut microbiota and bile acid profiles. Interventions targeting the gut microbiota-FXR signalling pathway may reduce DCA-induced intestinal disease.